L'apostasie dans le judaïsme - Gozlan, Eric (Convertirsi, de-convertirsi, riconvertirsi, 2016)
The history of Jewish people shows a great number of forced or sham conversions, due to the situation of diaspora and the social and juridical inferiority which came along with it. The phenomenon is particularly widespread in medieval and modern Spain, where the «marranos» (converted Jews) wishing to return in the Jewish community underwent penitential rituals. The problem of the re-admittance of converted Jews has gained a new interest because of the present claim of the descendants of marranos to be considered effectively Jews, especially with concern to marriage.